COVID-19: Financial Stress and Well-Being in Families. (May 2023) - Rodrigues, Margarida; Silva, Rui; Franco, Mário
In all areas of knowledge, research has shown the devastating effects of COVID-19, and the impact on families' financial stress and well-being is one of them. Crises are predictors of families' financial stress as they produce changes in their income and negative feelings, such as fear and demotivation, which affect well-being. This study analyses the financial and social impact of COVID-19 on families, supported by the ABCE-WB model, with data collection being the result of snowball sampling. The results obtained allow the conclusion that the current pandemic crisis has caused financial stress in families, to a greater or lesser degree, and caused feelings of fear and demotivation as consequences of the general lockdown. The empirical evidence also shows that these effects are positively associated with the perception of their level of well-being. The contribution of the study lies in corroborating the model used. Final considerations are presented together with the limitations and suggestions for future research.